Structural and Photophysical Investigation of Lanthanoid β-Triketonates - Reid, Brodie Lionel (Curtin University, 2015)
Reaction of β-triketonate ligands with lanthanoid cations in the presence of different bases results in the formation of structurally unique mononuclear and tetranuclear lanthanoid- species. The photophysical properties of the species were assessed in solid-state and solution, revealing bright visible or near infrared (NIR) emission. The NIR emission in particular was applied to the fabrication of a working NIR-organic light-emitting device (OLED). An α-nitrile β-diketonate Eu3+ complex was also investigated structurally, and spectroscopically.